A study on: why people patronize traditional bone setter over orthopedician and recommendation to orthopedicians. - Dr ABDUL HADI SHAREEF; Dr NARAYAN GUDI; Dr VISHAL HUGGI; Mrs. KHUDAIJA NAZHATH (International Journal of Pharma and Bio Sciences, 2017)
By observation of many complicated cases who arrive in our clinic after getting treated by traditional bone setter and lack of literature we are keen to evaluate reasons for preference to get treated by traditional bone setter and to derive conclusion for recommendation to Orhopedician for better treatment and patient care. We found Education is not a criterion for them to patronize traditional bone setter,Cost of treatment, availability in nearby area, all time availability, public transport facility, assurance giving, familiarity were criteria’s. Fear of going to Orhopedician for the reasons like: operation, hospitalization, cost, amputation criteria’s which made the difference to choice traditional bone setter.However most appreciated radiographic examination facility, and written instructions given by Orhopedicians.Open injured patients and major trauma patients preferred Orhopedician.Our study closely correlates with other studies in literature and final recommendations were: Improvements of patient doctor communication like assurance giving whenever needed are to be practiced frequently.Conservative management, surgery if needed has to be day care surgery, early discharge, limb saving procedure are to be encouraged.